Nursing and COVID-19 Ⅱ - Gray, Richard; Udod, Sonia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Nurses represent the highest number of healthcare workers globally and have played a critical role in the COVID-19 pandemic. This reprint highlights the issues and challenges faced by nurses practicing in hospital and community settings during the COVID-19 pandemic. The manuscripts herein focus on nurses in various areas of practice, including nurse managers, highlighting the impact, experience, and reality of providing care during the crisis. Interventions and strategies to support practice environments and the mental health and wellbeing of the nursing workforce were identified. Evidence from these manuscripts shed light on how nurse leaders can provide relevant, coordinated, and consistent organizational and leadership support to better establish a safe and healthy work environment that protects and fosters the mental health and wellbeing of all nursing personnel. The pandemic exacerbated the already demanding quality of work environments for nurses, as well as their mental health and wellbeing, thereby inducing a global nursing shortage; therefore, improving these factors, which ultimately influence nurse retention, is critical. We trust that sharing the lived experiences of nurses during the COVID-19 pandemic can enable us to leverage their expertise in meeting the complex care needs of patients, including COVID-19 patients, while improving the care needed by nurses in their working environments, alongside preparing for future pandemic waves.